Analisis implementasi kebijakan pemberian kompensasi dan reward bagi tenaga pendidik dan kependidikan di SDIT Al-Izhar School Pekanbaru - Shihabuddin, Ahmad; Saputri, Eki Nining; Hafis, Gustianto Nur; Fadel, Moh; Rahayu, Sri; Afriza, Afriza (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
This research aims to analyze the implementation of the compensation and reward policy for educators and education personnel at SDIT Al-Izhār School Pekanbaru. The compensation and reward policy designed by the Daar En Niswah Foundation is not only intended to motivate and appreciate performance, but also as an encouragement to increase spiritual values ​​for educators and education personnel at SDIT Al-Izhār School Pekanbaru. This study uses a descriptive qualitative approach method, where data collection is through interviews and document analysis. The results of this study illustrate that, in the implementation of the compensation and reward policy, in addition to having a positive impact, it also has a negative impact due to the unresolved obstacles. Thus, alternative solutions are needed to overcome existing obstacles and periodic evaluation of the implementation of the policy.